Psychology of Kidnapping - Anazonwu, Charles O; Onyemaechi, Chinwe Ifeyinwa; Igwilo, Chukwuemeka (Practicum Psychologia, 2018)
Huge resources through the government and private sectors have been allocated and reallocated to the task of preventing kidnapping. These efforts, however, often lack a conceptual, let alone empirical based foundation for understanding kidnappers and their acts of violence. This paper seeks to analyze and synthesize what has been reported from theoretical and empirical literature about the psychology of kidnapping. Based on a review of existing literature, and in an efforts to better understand the causes, motivations, and determinants of kidnapper behavior, this study analyzes key themes and findings on the psychology of kidnapping: (1) No single psychological theory has gained ascendance as an explanatory model for kidnapper violence. (2) Kidnapper violence most often is deliberate (not impulsive), strategic, and instrumental. (3) Perceived injustice, need for identify and need for belongings are common motives among potential kidnapers. (4) Mental illness is not a critical factor in explaining kidnapper behavior. Also most kidnappers are not psychopaths. (5) There is no kidnapper personality nor is there any accurate profile of the kidnapper. (6) Kidnapper beliefs tend to provide a set of values that justify and mandate certain behaviors. Those beliefs are regarded as absolute, and the behaviors are seen as serving a meaningful cause. Research on the psychology of kidnapping is embryonic at best. More research is needed to develop an evidence-based knowledge concerning the psychology of kidnappers.